Submerged Floating Tunnels under Seismic Motion: Vibration Mitigation and Seaquake effects. (2016) - Martinelli, Luca; Domaneschi, Marco; Shi, Chunxia
Abstract: In this work the activity of the research group active at Politecnico di Milano in the field of the dynamic behavior of Submerged Floating Tunnels (SFTs) is reviewed, with emphasis on the possibility to mitigate the dynamic response through structural control solutions and the modeling of seaquake effects. A SFT model, equipped with suitable passive control devices, is accounted as a case study to assess the vibration mitigation under strong seismic motions. Elastic-plastic axial springs restrain the tunnel at the shores, and bars made of inelastic material anchor the tunnel to the seabed. Earthquake and seaquake motions are introduced accounting for spatial variability of the seabed motion during an earthquake. Some conclusions are drawn from a comparison between the response of the case study SFT due to earthquake and earthquake plus seaquake, which point out as seaquake forces can be an important source of excitation for SFTs. The paucity of studies on this topic, as well as the extent of the effects induced, call for further researches and developments.